Find the gradients of y = 3x^2 − (2/3) x + 1 at x = 0

y = 3x^2 − (2/3) x + 1Derivative of 3x^2 = 6x3 * 2 = 6x^(2-1) = x^1 = xDerivative of -(2/3)x = -2/3-(2/3) * 1 = -2/3x^(1-1) = x^0 = 1dy/dx = 6x - 2/3at x = 0dy/dx = 6(0) - 2/3dy/dx = -2/3

Answered by Zaid B. Maths tutor

3042 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Curve D has equation 3x^2+2xy-2y^2+4=0 Find the equation of the tangent at point (2,4) and give your answer in the form ax+by+c=0, were a,b and c are integers.


A circle with center C has equation x^2 + y^2 + 8x - 12y = 12


What is a geometric series?


Find the stationary point of the function f(x) = x^2 +2x + 5


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences